Fast and convenient delivery of fluidextracts liquorice through electrospun core-shell nanohybrids - Liu, Hang; Dai, Yelin; Li, Jia; Liu, Ping; Zhou, Wenhui; Yu, Deng-Guang; Ge, Ruiliang (Frontiers in Bioengineering and Biotechnology, 2023)
As an interdisciplinary field, drug delivery relies more and more on the developments of modern science and technology. Correspondingly, how to upgrade the traditional dosage forms for a more efficacious, safer and more convenient drug delivery poses a continuous challenge to the researchers. In this study, a proof-of-concept demonstration was conducted for converting a popular traditional liquid dosage form (a commercial oral compound solution prepared from an intermediate Fluidextracts Liquorice) into a solid dosage form. The oral commercial solution was successfully encapsulated into the core-shell nanohybrids and the ethanol in the oral solution was removed. SEM and TEM evaluations showed that the prepared nanofibers had linear morphologies with out any discerned spindles or beads and an obvious core-shell nanostructure. FTIR and XRD results verified that the active ingredients in the commercial solution were compatible with the polymeric matrices and presented in the core section in an amorphous state. Three different types of methods were developed and the fast dissolution of electrospun core-shell nanofibers was verified. Coaxial electrospinning can act as a nano pharmaceutical technique for upgrading the traditional oral solution into fast dissolving solid drug delivery films to hold the advantages of liquid dosage forms and solid dosage forms.